PENEMPATAN TURBIN ANGIN OPTIMAL UNTUK GEDUNG PUSAT PEMBELAJARAN ARNTZ-GEISE 2 UNIVERSITAS KATOLIK PARAHYANGAN, BANDUNG UNTUK MENGHASILKAN ENERGI BERSIH SEPANJANG TAHUN - Gideon, Samuel; Purnama, Mimie (Riset Arsitektur (RISA), 2024)
Abstract-In today’s climate condition, green building technologi is no longer a luxury but a necessity. Wind is one of the natural resources that we can harvest using wind turbines to generate clean energy. Unfortunately, winds that blows in cities on tropical countries tends to have less speed than ones that blows in other climates and areas. Fortunately, winds speed can be manipulated through building orientation and forms to produce high speed winds that can be used by wind turbines to generate clean energy. There are many wind phenomenons that occurs due to building orientation and form, some of these phenomenons are: Wind Tunnel Effect, Cumulative Effect, and winds on the peaks of buildings. Other than that, buildings that have sharp edges tend to produce higher wind speeds than those that have curved edges. Pusat Pembelajaran Arntz-Geise 2 (PPAG 2) UNPAR, Bandung is a building that can produce these 4 phenomenons in order to generate high speed winds through its form and orientation. This evaluative research will analyze PPAG 2’s form againts winds that it will experience and evaluate where in the building are optimal spots to install wind turbines. The wind datas that will be used is a daily data throughout 2021. Those data will then be used as a base for wind simulations using the Computational Fluid Dynamics (CFD) Software. The results from the simulation will be analyzed to determine the optimal placements of wind turbines in order for PPAG 2 to generate clean energy year-round. The result of this research says that all outer edges of PPAG 2 is suitable for wind turbine placements, along with the top of both towers and the bridge connecting the northern and souther tower. Keywords: Wind Turbine, PPAG 2, placement, year-round, clean energy